2009
DOI: 10.1159/000229022
|View full text |Cite
|
Sign up to set email alerts
|

Selective versus Universal Screening for Gestational Diabetes Mellitus: An Evaluation of Naylor’s Model

Abstract: Aim: Selective screening for gestational diabetes is still a subject of debate. The aim of this study was to determine the effectiveness of a selective screening strategy for diagnosing gestational diabetes in our setting. This strategy rests on a scoring system that assigns women to different risk categories according to the presence of risk factors such as overweight, older age and ethnicity. Methods: We compared the rate of diagnosed gestational diabetes according to universal screening and selective screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…We expected a higher rate of GDM in Group A, similar to those reported by other authors who investigated GDM prevalence in the Belgian French-speaking Community, which varied from 5.2% [19] to 8% [11]. However, in both publications, the two-step GDM screening was done with classical Carpenter and Coustan criteria, which indicates that screening with a 75 g diagnostic OGTT might have been even more restrictive in the diagnosis of GDM than with a 100 g OGTT.…”
Section: Discussionsupporting
confidence: 89%
“…We expected a higher rate of GDM in Group A, similar to those reported by other authors who investigated GDM prevalence in the Belgian French-speaking Community, which varied from 5.2% [19] to 8% [11]. However, in both publications, the two-step GDM screening was done with classical Carpenter and Coustan criteria, which indicates that screening with a 75 g diagnostic OGTT might have been even more restrictive in the diagnosis of GDM than with a 100 g OGTT.…”
Section: Discussionsupporting
confidence: 89%
“…Much more research has considered the relative effectiveness of different screening methods at case finding rather than at improving clinical outcomes. Studies have variously suggested that universal screening identifies greater numbers of women with gestational diabetes than risk factor‐based screening [28,43,66,65], that 11% of cases may be missed if women with American Diabetes Association‐defined low risk are not tested [66] and that risk factor‐based screening is associated with low sensitivity and low specificity. Repeated random blood glucose tests at 4‐ to 6‐week intervals have been found to be equally sensitive but more specific than risk factor‐based methods for selecting women for diagnostic testing with oral glucose tolerance test [67], while universal screening with a 50‐g glucose challenge test has been found to be more sensitive than screening by risk factors [40] or random glucose tests [68].…”
Section: Resultsmentioning
confidence: 99%
“…The number-to-test varies between populations. For instance, in a study from Great Britain [25], the selective approach avoided testing in only 15% of women compared to universal screening and detected only 50% of cases of GDM. In a recent Italian study, where the prevalence of GDM was 11.1% with a universal screening policy, Pintaudi et al [26] found that the proportion with risk factors in their population was 58.3% and that 23% of cases of GDM would have been missed if selective screening criteria had been applied.…”
Section: Commentmentioning
confidence: 99%
“…They detected 75% of women with GDM using this statistical model as a screening tool, with a threshold of 2% as the predicted probability above which diagnostic testing (OGTT) was performed. In Naylor's model [25], a scoring system was based on age, BMI and ethnicity. In the large Atlantic DIP study in Ireland, in which GDM prevalence was 12.4% using International Association of Diabetes in Pregnancy Study Groups (IADPSG) criteria and universal screening, Avalos et al [31] retrospectively applied selective screening guidelines to their cohort.…”
Section: Commentmentioning
confidence: 99%